2022
DOI: 10.1007/jhep02(2022)061
|View full text |Cite
|
Sign up to set email alerts
|

Defect a-theorem and a-maximization

Abstract: Conformal defects describe the universal behaviors of a conformal field theory (CFT) in the presence of a boundary or more general impurities. The coupled critical system is characterized by new conformal anomalies which are analogous to, and generalize those of standalone CFTs. Here we study the conformal a- and c-anomalies of four dimensional defects in CFTs of general spacetime dimensions greater than four. We prove that under unitary defect renormalization group (RG) flows, the defect a-anomaly must decrea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 137 publications
(251 reference statements)
4
42
0
Order By: Relevance
“…Indeed, in section 5 we use the results of sections 3 and 4 to compute several defect central charges in two classes of examples. First are monodromy defects of free, massless scalars our Dirac fermions in d = 6, which also provide non-trivial tests of the defect a-theorem [39]. We also use the results for monodromy defects in free field theories to find defect central charges for conical defects and orbifolds.…”
Section: Jhep02(2022)166mentioning
confidence: 99%
See 4 more Smart Citations
“…Indeed, in section 5 we use the results of sections 3 and 4 to compute several defect central charges in two classes of examples. First are monodromy defects of free, massless scalars our Dirac fermions in d = 6, which also provide non-trivial tests of the defect a-theorem [39]. We also use the results for monodromy defects in free field theories to find defect central charges for conical defects and orbifolds.…”
Section: Jhep02(2022)166mentioning
confidence: 99%
“…In ref. [39], Wang showed that a Σ obeys an a-theorem, for RG flows localized to the defect, and furthermore, if the defect preserves at least N = 1 four-dimensional SUSY, then a Σ obeys a defect version of a-maximization.…”
Section: Jhep02(2022)166mentioning
confidence: 99%
See 3 more Smart Citations